Decadal Changes in Soil Organic Matter Due to Microaggregate and Hot Water Extractable Pools. Issue 1 (1st February 2019) - Lambie, Suzanne M.; Ghani, Anwar; Mudge, Paul L.; Stevenson, Bryan A.
Abstract : Core Ideas: Hot water extractable and microaggregate C explained 60% of soil C change over time. Hot water extractable and microaggregate N explained 47% of soil N change over time. No significant soil order effects on changes in C and N in fractions. Storage of C and N within aggregates is important for long‐term stabilization of soil organic matter (SOM). We investigated whether changes in C and N associated with physical soil fractions and the hot water extractable pool were correlated to changes in topsoil C and N over three decades. Archived soil samples from three soil orders collected from 46 sites across New Zealand were physically fractionated and the aggregate abundance (and C and N contents) of fractions determined; hot water extractable C (HWC) and hot water extractable N (HWN) were also measured. Together the change of C and N in hot water extractable SOM, microaggregate within macroaggregate, and free microaggregate fractions explained 60 and 47% of the change in whole soil C and N, respectively. Soil order was not a significant factor in the model suggesting that similar processes were operating in all three soil types. In summary, the development of strategies that enhance the storage of labile SOM and microaggregates could reverse the trend of loss of SOM and its associated ecosystems services.